The Relationship Between Employee Satisfaction and Corporate Financial Performance: A Systematic Review - Ginting, Erjayana; Nurhayati, Popong; Sukmawati, Anggraini (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to systematically review the relationship between employee satisfaction and corporate financial performance, examining the influence of various factors such as job satisfaction, work environment, compensation, and career development opportunities. It also explores mediating variables and contextual factors that moderate this relationship. A qualitative systematic review approach was employed, analyzing existing literature to identify key themes and relationships. The study focused on understanding how employee satisfaction influences financial performance, the mediating roles of motivation, productivity, and retention, and the moderating effects of company size, industry type, and geographic location. The review found that employee satisfaction significantly improves financial performance. Key factors such as job satisfaction, a positive work environment, fair compensation, and career development opportunities enhance employee satisfaction, boosting motivation, productivity, and retention. These mediating variables were found to impact financial performance positively. Additionally, contextual factors like company size, industry type, and geographic location moderate the strength of this relationship. Companies with supportive organizational cultures and robust employee satisfaction initiatives tend to perform better financially. The findings provide valuable insights for both academics and practitioners. Organizations can enhance financial performance by improving employee satisfaction through targeted strategies. This study also highlights the need for future research to explore the impact of emerging trends, such as remote work and technological advancements, on this relationship.